2015
DOI: 10.5993/ajhb.39.3.5
|View full text |Cite
|
Sign up to set email alerts
|

BMI and Smoking: Interrelated Factors among Cessation Website Users

Abstract: Smokers may currently have BMIs similar to the general population. BMI and CPD were positively correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…However, there is no significant difference observed between smokers and nonsmokers in terms of age and BMI in this study. The result is consistent with Schindler-Ruwisch et al [25] that reported smokers have BMIs similar to the general population, for instance nonsmoker population. One possible reason could be the difference between the averages age of the nonsmoker group and smoker group.…”
Section: Resultssupporting
confidence: 92%
“…However, there is no significant difference observed between smokers and nonsmokers in terms of age and BMI in this study. The result is consistent with Schindler-Ruwisch et al [25] that reported smokers have BMIs similar to the general population, for instance nonsmoker population. One possible reason could be the difference between the averages age of the nonsmoker group and smoker group.…”
Section: Resultssupporting
confidence: 92%
“…Similar studies have found the same results. Schindler-Ruwisch et al (2015), for instance, reported that the Mean BMI for never, intermittent, and daily cigarette smokers were 26.3, 27.4 and 28.1, respectively, reflecting that cigarette smokers had BMIs similar to the general population (Schindler-Ruwisch et al, 2015). Li et al's study (2010) on Mongolian population in China also did not provide any evidence to support an association between cigarette smoking and obesity.…”
Section: Discussionmentioning
confidence: 95%
“…The cigarette smoking is therefore presumed to correlate with lower BMI. Although, there is some evidence to support the negative association between smoking and weight-related outcomes (Schindler-Ruwisch et al, 2015), some health researchers have not confirmed any associations between obesity and smoking (Li et al, 2010). Often, the associations between cigarette smoking and obesity relies on data obtained from Body Mass Index (BMI) calculations; however, the likely trends of obesity have not yet been well-quantified using measured BMI.…”
Section: Introductionmentioning
confidence: 99%
“…In advanced cases, on the other hand, malnourishment and low BMI pose a serious threat to overall health and can have negative effects on tumor therapy (39,40). Tobacco smoking can be associated with low socioeconomic status and higher BMI but also coincided with lower BMI in other studies (41)(42)(43). A poor diet, low in fruit and vegetables, has been correlated with oral cancer, and it has been shown that a Mediterranean diet favorably affects the risk of upper aerodigestive tract cancer (44,45).…”
Section: Discussionmentioning
confidence: 98%